Soft magnetic alloy material and preparation method and application thereof

By covering the core-shell structure soft magnetic alloy material with silicon oxide, silicate and silicone resin layers on the surface of the alloy powder, the problems of low magnetic permeability and high loss in the prior art are solved, and the performance of high Q value, low loss and high saturation current is achieved, which is suitable for thinning and miniaturization of electronic products.

CN119694703APending Publication Date: 2025-03-25SHENZHEN SUNLORD ELECTRONICS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411894120.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The prior art is difficult to take into account both high permeability, low loss and high saturation current, especially in servers and terminal equipment, with higher requirements for large current and low loss.

Method used

The soft magnetic alloy material adopts a core-shell structure, by sequentially covering the insulated silicon oxide layer, silicate layer and silicone resin layer on the surface of the alloy powder, the formed material has high Q value, high saturation current and low loss performance in the frequency range of 100 kHz-1 MHz.

Benefits of technology

The product size under the same sense amount is smaller and thinner, and the energy conversion efficiency is higher, which meets the needs of thinner and miniaturization of electronic products, and solves the problems of low permeability and high loss of traditional molded inductor powders.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119694703A_ABST
    Figure CN119694703A_ABST
Patent Text Reader

Abstract

The invention provides a magnetically soft alloy material and a preparation method and application thereof.The magnetically soft alloy material is of a core-shell structure and comprises an alloy core and an insulating coating layer set; wherein the insulating coating layer group comprises a silicon oxide layer, a silicate layer and an organic silicon resin layer which are stacked, and the silicon oxide layer is arranged on the surface of the alloy core. The soft magnetic alloy material provided by the invention has the performance of high Q value, high saturation current and low loss in the frequency range of 100kHz-1MHz, solves the problems of low magnetic conductivity and high loss of the traditional mould pressing inductance powder, and is beneficial to large-scale popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft magnetic materials, and relates to a soft magnetic alloy material, and in particular to a soft magnetic alloy material and a preparation method and application thereof. Background Art

[0002] With the rapid development of science and technology, the market demand for electronic products is developing towards lighter, thinner and smaller products. As a core component of electronic products, the material performance of inductors needs to meet very high requirements, especially in servers and terminal devices. People have higher requirements for inductor products with large current, low loss, high conversion efficiency and heat dissipation performance. Among them, the Q value is an important parameter to describe the performance of inductance, which indicates the ratio of the inductive reactance presented by the inductor to its equivalent loss resistance when it works at an AC voltage of a specific frequency. The higher the Q value, the better the inductor performs in storing energy, the smaller the loss, and therefore the better its performance. Therefore, in order to solve the above problems, it is of great significance to develop a new high-Q value soft magnetic alloy material.

[0003] At present, most one-piece molded inductors use iron-silicon-chromium alloy powder or carbonyl iron powder as raw materials. However, whether iron-silicon-chromium alloy powder or carbonyl iron powder is used, it is impossible to take into account the magnetic permeability, saturation current and loss at the same time, and there are certain defects. Especially in servers and terminal equipment, the requirements for high current and low loss are higher, and traditional molded inductors are difficult to meet the requirements.

[0004] CN111063501A discloses a method for preparing low-loss powder for producing one-piece molded inductors, specifically, carbonyl iron powder is mixed with iron silicon powder or amorphous powder and then coated and granulated. However, iron silicon has high loss in soft magnetic alloy materials, and iron silicon accounts for a high proportion in the mixed powder. The performance of amorphous powder needs to be annealed at a higher temperature (370-380°C) to achieve its optimal performance, while the heat treatment temperature of the above patent is 90-120°C, so the obtained powder is still difficult to achieve the goal of high magnetic permeability and low loss.

[0005] CN114255952A discloses a low-loss powder for integrally molded inductors and a preparation method thereof. The powder mainly improves magnetic permeability and reduces loss by adopting sendustine and carbonyl iron powder grading. However, the above scheme still cannot produce a material with high Q value and low loss.

[0006] It can be seen that how to provide a soft magnetic alloy material with high Q value, high saturation current and low loss and a preparation method thereof has become an urgent problem that technical personnel in this field need to solve. Summary of the invention

[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a soft magnetic alloy material and a preparation method and application thereof. The soft magnetic alloy material has the performance of high Q value, high saturation current and low loss in the frequency range of 100kHz-1MHz, which solves the problems of low magnetic permeability and high loss of traditional molded inductor powder, and is conducive to large-scale promotion and application.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a soft magnetic alloy material, wherein the soft magnetic alloy material is a core-shell structure, including an alloy core and an insulating coating layer group.

[0010] The insulating coating layer group includes a stacked silicon oxide layer, a silicate layer and a silicone resin layer, and the silicon oxide layer is arranged on the surface of the alloy core.

[0011] The present invention sequentially coats an insulating silicon oxide layer, a silicate layer and a silicone resin layer on the surface of an alloy powder, and the obtained soft magnetic alloy material has the performance of high Q value, high saturation current and low loss in the frequency range of 100kHz-1MHz. Under the same inductance, the product can be made smaller and thinner, and the product energy conversion efficiency is higher, which meets the needs of lightweight and miniaturized electronic products, effectively solves the problems of low magnetic permeability and high loss of traditional molded inductor powder, and is conducive to large-scale promotion and application.

[0012] In the present invention, the components of the alloy core include: Fe 45-55wt%, Ni 45-55wt%, Si 2.0-5.5wt%, Al 2.0-5.0wt%, and C 0.05-0.5wt%.

[0013] And / or, the alloy core has a D50 particle size of 5-15 μm, and a D90 particle size of ≤25 μm.

[0014] In the present invention, the average thickness of the silicon oxide layer is 10nm-20nm.

[0015] And / or, the silicate in the silicate layer includes sodium silicate and / or potassium silicate.

[0016] And / or, the average thickness of the silicate layer is 10 nm-20 nm.

[0017] And / or, the organic silicone resin in the organic silicone resin layer is a modified organic silicone resin, specifically including any one of KR-511, KR-510, KR-500, KR-216 or KR-213, or a combination of at least two thereof.

[0018] And / or, the average thickness of the silicone resin layer is 10 nm-20 nm.

[0019] In a second aspect, the present invention provides a method for preparing the soft magnetic alloy material as described in the first aspect, the preparation method comprising the following steps:

[0020] (1) preparing alloy powder by atomization method;

[0021] (2) coating the alloy powder with tetraethyl orthosilicate, modified water glass and modified silicone resin in sequence to obtain alloy coated powder;

[0022] (3) The alloy-coated powder is subjected to spray granulation, pressing molding and reduction roasting in sequence to obtain a soft magnetic alloy material.

[0023] In the present invention, the atomization method in step (1) comprises: smelting the metal raw material into molten metal, generating metal droplets through the spraying action of an atomizing nozzle, and obtaining alloy powder after cooling and solidification.

[0024] Wherein, the metal raw materials include iron, nickel, silicon and aluminum.

[0025] In the present invention, the tetraethyl orthosilicate coating in step (2) comprises: mixing alloy powder and tetraethyl orthosilicate solution, and sequentially air-drying, drying and sieving to obtain a first powder.

[0026] The tetraethyl orthosilicate solution is a mixed solution of tetraethyl orthosilicate and ammonia water, and the content of the tetraethyl orthosilicate is 0.5-1.5wt%.

[0027] In the present invention, the modified water glass coating in step (2) comprises: mixing the first powder and the modified water glass solution, and sequentially air-drying, drying and sieving to obtain the second powder.

[0028] The modified water glass solution is a mixed solution of water glass and a modifier, and the content of the water glass is 0.3-1.0wt%.

[0029] And / or, the modified water glass includes modified sodium water glass and / or modified potassium water glass, and the modification method includes any one of doping modification, polymerization modification or sulfidation modification.

[0030] In the present invention, the modified silicone resin coating in step (2) comprises: mixing the second powder and the modified silicone resin solution, and sequentially air-drying, drying and sieving to obtain alloy-coated powder.

[0031] The modified silicone resin solution is a mixed solution of modified silicone resin and an organic solvent, and the organic solvent includes any one of acetone, ethyl acetate or toluene or a combination of at least two thereof, and the content of the modified silicone resin is 0.5-2.0 wt %.

[0032] In the present invention, the spray granulation in step (3) comprises: mixing the alloy coated powder and the polyvinyl butyral solution for spray granulation, cooling and sieving to obtain granulated powder.

[0033] The polyvinyl butyral solution is a mixed solution of polyvinyl butyral and acetone, and the content of the polyvinyl butyral is 1.0-4.0wt%.

[0034] And / or, the reduction roasting in step (3) is carried out in an atmosphere of hydrogen or a hydrogen-nitrogen mixture.

[0035] In a third aspect, the present invention provides an application of the soft magnetic alloy material as described in the first aspect, wherein the soft magnetic alloy material is used to manufacture an integrally formed inductor.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The present invention sequentially coats an insulating silicon oxide layer, a silicate layer and a silicone resin layer on the surface of an alloy powder, and the obtained soft magnetic alloy material has the performance of high Q value, high saturation current and low loss in the frequency range of 100kHz-1MHz. Under the same inductance, the product can be made smaller and thinner, and the product energy conversion efficiency is higher, which meets the needs of lightweight and miniaturized electronic products, effectively solves the problems of low magnetic permeability and high loss of traditional molded inductor powder, and is conducive to large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 It is a schematic diagram of the structure of the soft magnetic alloy material provided by the present invention.

[0039] Among them: 10 - alloy core; 20 - insulating coating layer group; 21 - silicon oxide layer; 22 - silicate layer; 23 - silicone resin layer. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0041] A certain embodiment of the present invention provides a soft magnetic alloy material, such as Figure 1 As shown, the soft magnetic alloy material is a core-shell structure, including an alloy core 10 and an insulating coating layer group 20.

[0042] The insulating coating layer group 20 includes a stacked silicon oxide layer 21 , a silicate layer 22 and a silicone resin layer 23 , and the silicon oxide layer 21 is disposed on the surface of the alloy core 10 .

[0043] Specifically, the silicon oxide layer 21 can improve the thermal stability, electrical insulation and oxidation resistance of the metal powder; the silicate layer 22 can improve the heat resistance, acid resistance and adhesion of the metal powder; and the silicone resin layer 23 can improve the electrical insulation, high temperature resistance and corrosion resistance of the metal powder.

[0044] The present invention sequentially coats the surface of the alloy powder with an insulating silicon oxide layer 21, a silicate layer 22 and a silicone resin layer 23, and the resulting soft magnetic alloy material has the performance of high Q value, high saturation current and low loss in the frequency range of 100kHz-1MHz. Under the same inductance, the product can be made smaller and thinner, and the product energy conversion efficiency is higher, which meets the needs of lightweight and miniaturized electronic products, effectively solves the problems of low magnetic permeability and high loss of traditional molded inductor powder, and is conducive to large-scale promotion and application.

[0045] In some embodiments, the composition of the alloy core 10 includes: Fe 45-55wt%, such as 45wt%, 46wt%, 47wt%, 48wt%, 49wt%, 50wt%, 51wt%, 52wt%, 53wt%, 54wt% or 55wt%, and more preferably 45-50wt%; Ni 45-55wt%, such as 45wt%, 46wt%, 47wt%, 48wt%, 49wt%, 50wt%, 51wt%, 52wt%, 53wt%, 54wt% or 55wt%, and more preferably 45-50wt%; Si 2.0-5.5wt%, such as 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt% or 5.5wt%, and more preferably 3.0-4.5wt%; Al 2.0-5.0wt%, for example, it can be 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt% or 5.0wt%, and more preferably 2.5-4.0wt%; C 0.05-0.5wt%, for example, it can be 0.05wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt% or 0.5wt%, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0046] In some embodiments, the D50 particle size of the alloy core 10 is 5-15μm, for example, it can be 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm or 15μm, and the D90 particle size is ≤25μm, for example, it can be 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm or 25μm, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] In some embodiments, the average thickness of the silicon oxide layer 21 is 10nm-20nm, for example, it can be 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm or 20nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] In certain embodiments, the silicate in the silicate layer 22 includes sodium silicate and / or potassium silicate.

[0049] In some embodiments, the average thickness of the silicate layer 22 is 10nm-20nm, for example, it can be 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm or 20nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] In some embodiments, the silicone resin in the silicone resin layer 23 is a modified silicone resin, specifically including any one of KR-511, KR-510, KR-500, KR-216 or KR-213, or a combination of at least two of them. Typical but non-limiting combinations include a combination of KR-511 and KR-510, a combination of KR-510 and KR-500, a combination of KR-500 and KR-216, or a combination of KR-216 and KR-213.

[0051] In some embodiments, the average thickness of the silicone resin layer 23 is 10nm-20nm, for example, it can be 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm or 20nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] A certain embodiment of the present invention provides a method for preparing the above-mentioned soft magnetic alloy material, the preparation method comprising the following steps:

[0053] (1) preparing alloy powder by atomization method;

[0054] (2) coating the alloy powder with tetraethyl orthosilicate, modified water glass and modified silicone resin in sequence to obtain alloy coated powder;

[0055] (3) The alloy-coated powder is subjected to spray granulation, pressing molding and reduction roasting in sequence to obtain a soft magnetic alloy material.

[0056] In certain embodiments, the atomization method in step (1) includes: smelting the metal raw material into molten metal, generating metal droplets through the spraying action of an atomizing nozzle, and obtaining alloy powder after cooling and solidification.

[0057] Wherein, the metal raw materials include iron, nickel, silicon and aluminum.

[0058] In some embodiments, the tetraethyl orthosilicate coating in step (2) includes: mixing the alloy powder and the tetraethyl orthosilicate solution, and sequentially air-drying, drying and sieving to obtain a first powder.

[0059] Wherein, the tetraethyl orthosilicate solution is a mixed solution of tetraethyl orthosilicate and ammonia water, and the content of the tetraethyl orthosilicate is 0.5-1.5wt%, for example, it can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt% or 1.5wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0060] In certain embodiments, the modified water glass coating in step (2) comprises: mixing a first powder and a modified water glass solution, and sequentially air-drying, drying and sieving to obtain a second powder.

[0061] Among them, the modified water glass solution is a mixed solution of water glass and a modifier, and the content of the water glass is 0.3-1.0wt%, for example, it can be 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt% or 1.0wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0062] In certain embodiments, the modified water glass includes modified sodium water glass and / or modified potassium water glass, and the modification method includes any one of doping modification, polymerization modification or sulfurization modification.

[0063] In the present invention, the doping modification is specifically: adding an appropriate amount of phosphate, aluminate, titanate, etc. to water glass, wherein the phosphate, aluminate, and titanate are modifiers; the polymerization modification is specifically: adding an appropriate amount of polyethylene glycol, polyacrylamine, polyacrylic acid, etc. to water glass, wherein the polyethylene glycol, polyacrylamine, and polyacrylic acid are modifiers; the vulcanization modification is specifically: adding an appropriate amount of vulcanizing agent to water glass, wherein the vulcanizing agent is the modifier.

[0064] In certain embodiments, the modified silicone resin coating in step (2) includes: mixing the second powder and the modified silicone resin solution, and sequentially air-drying, drying and sieving to obtain alloy-coated powder.

[0065] The modified silicone resin solution is a mixed solution of a modified silicone resin and an organic solvent, and the organic solvent includes any one of acetone, ethyl acetate or toluene or a combination of at least two thereof, and typical but non-limiting combinations include a combination of acetone and ethyl acetate, a combination of ethyl acetate and toluene, a combination of acetone and toluene, or a combination of acetone, ethyl acetate and toluene; the content of the modified silicone resin is 0.5-2.0wt%, for example, it can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt% or 2.0wt%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0066] In some embodiments, the air-drying is carried out by fan air-drying; the drying temperature is 80-100°C, for example, it can be 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C, 96°C, 98°C or 100°C, and the drying time is 0.5-2h, for example, it can be 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2h; the screening mesh size is 20-80 mesh, for example, it can be 20 mesh, 30 mesh, 40 mesh, 50 mesh, 60 mesh, 70 mesh or 80 mesh, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0067] In certain embodiments, the spray granulation in step (3) comprises: mixing the alloy coated powder and the polyvinyl butyral solution for spray granulation, cooling and sieving to obtain granulated powder.

[0068] The polyvinyl butyral solution is a mixed solution of polyvinyl butyral and acetone, and the content of the polyvinyl butyral is 1.0-4.0wt%, for example, it can be 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt% or 4.0wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0069] In some embodiments, the cooling method is natural cooling; the screening mesh size is 60-400 mesh, for example, it can be 60 mesh, 80 mesh, 100 mesh, 150 mesh, 200 mesh, 250 mesh, 300 mesh, 350 mesh or 400 mesh, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0070] In certain embodiments, the air inlet temperature of the spray granulation in step (3) is 100-200°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, and the air outlet temperature is 60-100°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are equally applicable.

[0071] In certain embodiments, the applied pressure for the press molding in step (3) is 1000-2000 MPa, for example, 1000 MPa, 1100 MPa, 1200 MPa, 1300 MPa, 1400 MPa, 1500 MPa, 1600 MPa, 1700 MPa, 1800 MPa, 1900 MPa or 2000 MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0072] In certain embodiments, the reduction calcination in step (3) is performed in an atmosphere of hydrogen or a hydrogen-nitrogen mixture.

[0073] In certain embodiments, the reduction roasting temperature in step (3) is 700-750°C, for example, 700°C, 705°C, 710°C, 715°C, 720°C, 725°C, 730°C, 735°C, 740°C, 745°C or 750°C; the roasting time is 2-6h, for example, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h; the holding time is 1-3h, for example, 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h, 2.2h, 2.4h, 2.6h, 2.8h or 3h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0074] A certain embodiment of the present invention provides an application of the soft magnetic alloy material, which is specifically used for manufacturing an integrally formed inductor.

[0075] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0076] Example 1

[0077] This embodiment provides a soft magnetic alloy material and a preparation method thereof, the preparation method comprising the following steps:

[0078] (1) Metal raw materials were weighed according to Fe 46wt%, Ni 45wt%, Si 4.5wt%, Al 4.3wt%, and C 0.2wt%, and were placed in a high-temperature smelting furnace to be smelted into molten metal. The molten metal was sprayed into an atomizing tower through a high-speed airflow and spherical metal droplets were generated through the spraying action of an atomizing nozzle. After rapid cooling and solidification, alloy powders with a D50 particle size of 10μm and a D90 particle size of 16μm were obtained.

[0079] (2) performing insulation coating treatment on the alloy powder, specifically comprising:

[0080] (2.1) mixing tetraethyl orthosilicate and ammonia water to obtain a tetraethyl orthosilicate solution, wherein the content of the tetraethyl orthosilicate is 0.75wt%; mixing the alloy powder and the tetraethyl orthosilicate solution, and sequentially subjecting the mixture to fan drying, drying at 100° C. for 1 hour, and sieving through 30 meshes to obtain a first powder;

[0081] (2.2) Mix sodium water glass and polyacrylamine (M w ≈65000) for polymerization modification to obtain a modified water glass solution, wherein the content of the sodium water glass is 0.3wt%; mixing the first powder and the modified water glass solution, and sequentially subjecting the mixture to fan drying, drying at 100° C. for 1 h, and 30 mesh sieving to obtain a second powder;

[0082] (2.3) Mixing modified silicone resin KR-511 and acetone to obtain a modified silicone resin solution, wherein the content of KR-511 is 0.5wt%; mixing the second powder and the modified silicone resin solution, and successively subjecting them to fan drying, drying at 100°C for 1h and 30 mesh sieving to obtain an alloy coated powder.

[0083] (3) Mixed polyvinyl butyral (M w ≈35000) and acetone to obtain a polyvinyl butyral solution, wherein the content of the polyvinyl butyral is 3.0wt%; the alloy coated powder and the polyvinyl butyral solution are mixed for spray granulation, the air inlet temperature is controlled at 150°C, the air outlet temperature is controlled at 80°C, and the granulated powder is obtained after natural cooling and 200 mesh sieving.

[0084] (4) Add 2 wt‰ zinc stearate to the granulated powder, mix well, apply a pressure of 1300 MPa to press into shape, and then reduce and calcine in an atmosphere of hydrogen and nitrogen mixed gas (volume ratio of 2:8), control the calcination temperature to 720 ° C, the calcination time to 4 h, and the insulation time to 2 h to obtain a soft magnetic alloy material.

[0085] It can be seen from the above preparation method that the soft magnetic alloy material provided in this embodiment is a core-shell structure, including an alloy core and an insulating coating layer group. The insulating coating layer group includes a stacked silicon oxide layer, a sodium silicate layer and a silicone resin layer, and the silicon oxide layer is arranged on the surface of the alloy core.

[0086] According to the detection by scanning electron microscope, in the soft magnetic alloy material obtained in this embodiment, the average thickness of the silicon oxide layer is 12.8 nm, the average thickness of the sodium silicate layer is 10.6 nm, and the average thickness of the silicone resin layer is 11.1 nm.

[0087] Example 2

[0088] This embodiment provides a soft magnetic alloy material and a preparation method thereof, the preparation method comprising the following steps:

[0089] (1) Metal raw materials are weighed according to Fe 45wt%, Ni 45wt%, Si 5.0wt%, Al 4.5wt%, and C 0.5wt%, and are placed in a high-temperature smelting furnace to be smelted into molten metal. The molten metal is sprayed into an atomizing tower through a high-speed airflow and spherical metal droplets are generated through the spraying action of an atomizing nozzle. After rapid cooling and solidification, alloy powders with a D50 particle size of 15μm and a D90 particle size of 20μm are obtained.

[0090] (2) performing insulation coating treatment on the alloy powder, specifically comprising:

[0091] (2.1) mixing tetraethyl orthosilicate and ammonia water to obtain a tetraethyl orthosilicate solution, wherein the content of the tetraethyl orthosilicate is 0.5wt%; mixing the alloy powder and the tetraethyl orthosilicate solution, sequentially subjecting the mixture to fan drying, drying at 100° C. for 1 hour, and sieving through 30 meshes to obtain a first powder;

[0092] (2.2) Mix sodium water glass and polyacrylamine (M w ≈65000) for polymerization modification to obtain a modified water glass solution, wherein the content of the sodium water glass is 0.6wt%; mixing the first powder and the modified water glass solution, and sequentially subjecting the mixture to fan drying, drying at 100° C. for 1 h, and 30 mesh sieving to obtain a second powder;

[0093] (2.3) Mixing modified silicone resin KR-510 and acetone to obtain a modified silicone resin solution, wherein the content of KR-510 is 1.2 wt%; mixing the second powder and the modified silicone resin solution, and sequentially subjecting the mixture to fan drying, drying at 100° C. for 1 h, and 30 mesh sieving to obtain an alloy coated powder.

[0094] (3) Mixed polyvinyl butyral (M w ≈35000) and acetone to obtain a polyvinyl butyral solution, wherein the content of the polyvinyl butyral is 1.0wt%; the alloy coated powder and the polyvinyl butyral solution are mixed for spray granulation, the air inlet temperature is controlled at 100°C, the air outlet temperature is controlled at 60°C, and the granulated powder is obtained after natural cooling and 200 mesh sieving.

[0095] (4) Add 2 wt‰ zinc stearate to the granulated powder, mix well, apply a pressure of 1000 MPa for pressing, and then reduce and calcine in an atmosphere of hydrogen and nitrogen mixed gas (volume ratio of 2:8), control the calcination temperature to 700 ° C, the calcination time to 6 h, and the insulation time to 3 h to obtain a soft magnetic alloy material.

[0096] It can be seen from the above preparation method that the soft magnetic alloy material provided in this embodiment is a core-shell structure, including an alloy core and an insulating coating layer group. The insulating coating layer group includes a stacked silicon oxide layer, a sodium silicate layer and a silicone resin layer, and the silicon oxide layer is arranged on the surface of the alloy core.

[0097] According to the detection by scanning electron microscope, in the soft magnetic alloy material obtained in this embodiment, the average thickness of the silicon oxide layer is 11.9 nm, the average thickness of the sodium silicate layer is 12.4 nm, and the average thickness of the silicone resin layer is 14.8 nm.

[0098] Example 3

[0099] This embodiment provides a soft magnetic alloy material and a preparation method thereof, the preparation method comprising the following steps:

[0100] (1) Metal raw materials are weighed according to Fe 45wt%, Ni 49wt%, Si 3.4wt%, Al 2.5wt%, and C 0.1wt%, and are placed in a high-temperature smelting furnace to be smelted into molten metal. The molten metal is sprayed into an atomizing tower through a high-speed airflow and spherical metal droplets are generated through the spraying action of an atomizing nozzle. After rapid cooling and solidification, alloy powders with a D50 particle size of 5μm and a D90 particle size of 20μm are obtained.

[0101] (2) performing insulation coating treatment on the alloy powder, specifically comprising:

[0102] (2.1) mixing tetraethyl orthosilicate and ammonia water to obtain a tetraethyl orthosilicate solution, wherein the content of the tetraethyl orthosilicate is 1.5 wt %; mixing the alloy powder and the tetraethyl orthosilicate solution, sequentially subjecting the mixture to fan drying, drying at 100° C. for 1 h, and sieving through 30 meshes to obtain a first powder;

[0103] (2.2) Mix sodium water glass and polyacrylamine (M w ≈65000) for polymerization modification to obtain a modified water glass solution, wherein the content of the sodium water glass is 1.0wt%; mixing the first powder and the modified water glass solution, and sequentially subjecting the mixture to fan drying, drying at 100° C. for 1 hour, and 30 mesh sieving to obtain a second powder;

[0104] (2.3) Mixing modified silicone resin KR-500 and acetone to obtain a modified silicone resin solution, wherein the content of KR-500 is 2.0 wt%; mixing the second powder and the modified silicone resin solution, and successively subjecting them to fan drying, drying at 100° C. for 1 h, and 30 mesh sieving to obtain an alloy coated powder.

[0105] (3) Mixed polyvinyl butyral (M w ≈35000) and acetone to obtain a polyvinyl butyral solution, wherein the content of the polyvinyl butyral is 4.0wt%; the alloy coated powder and the polyvinyl butyral solution are mixed for spray granulation, the air inlet temperature is controlled at 200°C, the air outlet temperature is controlled at 100°C, and the granulated powder is obtained after natural cooling and 200 mesh sieving.

[0106] (4) Add 2 wt‰ zinc stearate to the granulated powder, mix well, apply a pressure of 2000 MPa for pressing, and then reduce and calcine in an atmosphere of hydrogen and nitrogen mixed gas (volume ratio of 2:8), control the calcination temperature to 750°C, the calcination time to 2 h, and the insulation time to 1 h to obtain a soft magnetic alloy material.

[0107] It can be seen from the above preparation method that the soft magnetic alloy material provided in this embodiment is a core-shell structure, including an alloy core and an insulating coating layer group. The insulating coating layer group includes a stacked silicon oxide layer, a sodium silicate layer and a silicone resin layer, and the silicon oxide layer is arranged on the surface of the alloy core.

[0108] According to the detection by scanning electron microscope, in the soft magnetic alloy material obtained in this embodiment, the average thickness of the silicon oxide layer is 16.9 nm, the average thickness of the sodium silicate layer is 13.3 nm, and the average thickness of the silicone resin layer is 15.5 nm.

[0109] Example 4

[0110] The present embodiment provides a soft magnetic alloy material and a preparation method thereof. Except for changing the composition of the metal raw material described in step (1) to: Fe 49wt%, Ni 45wt%, Si 3.0wt%, Al 2.7wt%, C 0.3wt%, the remaining steps and conditions are the same as those in Example 1, and therefore are not described in detail here.

[0111] Example 5

[0112] The present embodiment provides a soft magnetic alloy material and a preparation method thereof. Except for changing the composition of the metal raw material described in step (1) to: Fe 46wt%, Ni 46wt%, Si 4.0wt%, Al 4.0wt%, the remaining steps and conditions are the same as those in Example 1, and thus are not described in detail here.

[0113] Comparative Example 1

[0114] This comparative example provides a soft magnetic alloy material and a preparation method thereof, except that step (2.1) is not performed, that is, the alloy powder is not coated with tetraethyl orthosilicate, but only modified water glass coating and modified silicone resin coating are performed. The remaining steps and conditions are the same as those in Example 1, so they are not repeated here.

[0115] Comparative Example 2

[0116] This comparative example provides a soft magnetic alloy material and a preparation method thereof, except that step (2.2) is not performed, that is, the alloy powder is not coated with modified water glass, but only coated with tetraethyl orthosilicate and modified silicone resin. The remaining steps and conditions are the same as those in Example 1, so they are not repeated here.

[0117] Comparative Example 3

[0118] This comparative example provides a soft magnetic alloy material and a preparation method thereof, except that step (2.3) is not performed, that is, the alloy powder is not coated with a modified silicone resin, but only coated with tetraethyl orthosilicate and modified water glass. The remaining steps and conditions are the same as those in Example 1, so they are not repeated here.

[0119] Comparative Example 4

[0120] This comparative example provides a soft magnetic alloy material and a preparation method thereof, the preparation method comprising the following steps:

[0121] (1) 200 g of atomized iron-silicon-chromium powder with a D50 particle size of 15 μm was selected, wherein Fe accounted for 90 wt %, Si accounted for 4.5 wt %, and Cr accounted for 5.5 wt %.

[0122] (2) atomized iron-silicon-chromium powder and 3.0 wt% epoxy resin are granulated, dried at 80° C., and then sieved through 200 meshes to obtain granulated powder.

[0123] (3) Add 2 wt‰ zinc stearate to the granulated powder, mix well, apply a pressure of 1300 MPa to press into shape, and then reduce and calcine in an atmosphere of hydrogen and nitrogen mixed gas (volume ratio of 2:8), control the calcination temperature to 720 ° C, the calcination time to 4 h, and the insulation time to 2 h to obtain a soft magnetic alloy material.

[0124] Comparative Example 5

[0125] This comparative example provides a soft magnetic alloy material and a preparation method thereof, the preparation method comprising the following steps:

[0126] (1) selecting aerosolized iron-silicon-chromium powder with a D50 particle size of 15 μm and carbonyl iron powder with a D50 particle size of 6 μm, and grading them in a mass ratio of 7:3 to obtain graded powder;

[0127] (2) Granulate the graded powder and 3.0 wt% epoxy resin, dry at 80°C, and then sieve through 200 meshes to obtain granulated powder.

[0128] (3) Add 2 wt‰ zinc stearate to the granulated powder, mix well, apply a pressure of 1300 MPa to press into shape, and then reduce and calcine in an atmosphere of hydrogen and nitrogen mixed gas (volume ratio of 2:8), control the calcination temperature to 720 ° C, the calcination time to 4 h, and the insulation time to 2 h to obtain a soft magnetic alloy material.

[0129] Performance Testing

[0130] The soft magnetic alloy materials obtained in Examples 1-5 and Comparative Examples 1-5 were used to prepare magnetic rings with an outer diameter (OD) × inner diameter (ID) × thickness (TH) = 8.0 mm × 5.0 mm × 2.0 mm, and the performance of the magnetic rings was evaluated. Copper wire, winding turns N = 26Ts, use WK6500B LCR tester to test the inductance, Q value and inductance value under superposition current of the magnetic ring sample, the test frequency is 1MHz / 1V, and IWATSU-SY-8218 hysteresis loop meter is used to test the power consumption of the magnetic ring (50mT&1MHz). The relevant test results are shown in Table 1 below.

[0131] Table 1

[0132]

[0133]

[0134] It can be seen that the present invention designs the alloy powder composition and particle size, and sequentially coats the powder surface with an insulating silicon oxide layer, a silicate layer and a silicone resin layer, so that the obtained soft magnetic alloy material has the performance of high Q value, high saturation current and low loss in the frequency range of 100kHz-1MHz. Under the same inductance, the product can be made smaller and thinner, and the product energy conversion efficiency is higher, which meets the needs of lightweight and miniaturized electronic products, effectively solves the problems of low magnetic permeability and high loss of traditional molded inductor powder, and is conducive to large-scale promotion and application.

[0135] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A soft magnetic alloy material, characterized in that: The soft magnetic alloy material is a core-shell structure, including an alloy core and an insulating coating layer group; The insulating coating layer group includes a stacked silicon oxide layer, a silicate layer and a silicone resin layer, and the silicon oxide layer is arranged on the surface of the alloy core.

2. The soft magnetic alloy material according to claim 1, characterized in that: The alloy core comprises: Fe 45-55wt%, Ni 45-55wt%, Si 2.0-5.5wt%, Al 2.0-5.0wt%, C 0.05-0.5wt%; And / or, the alloy core has a D50 particle size of 5-15 μm, and a D90 particle size of ≤25 μm.

3. The soft magnetic alloy material according to claim 1 or 2, characterized in that: The average thickness of the silicon oxide layer is 10nm-20nm; And / or, the silicate in the silicate layer is sodium silicate and / or potassium silicate; and / or, the average thickness of the silicate layer is 10 nm to 20 nm; And / or, the organic silicone resin in the organic silicone resin layer is a modified organic silicone resin, specifically including any one of KR-511, KR-510, KR-500, KR-216 or KR-213 or a combination of at least two thereof; And / or, the average thickness of the organic silicone resin layer is 10nm-20nm.

4. A method for preparing the soft magnetic alloy material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) preparing alloy powder by atomization method; (2) coating the alloy powder with tetraethyl orthosilicate, modified water glass and modified silicone resin in sequence to obtain alloy coated powder; (3) The alloy-coated powder is subjected to spray granulation, pressing molding and reduction roasting in sequence to obtain a soft magnetic alloy material.

5. The preparation method according to claim 4, characterized in that: The atomization method in step (1) comprises: smelting the metal raw material into a molten metal, generating metal droplets through the spraying action of an atomizing nozzle, and obtaining alloy powder after cooling and solidification; Wherein, the metal raw materials include iron, nickel, silicon and aluminum.

6. The preparation method according to claim 4 or 5, characterized in that: The tetraethyl orthosilicate coating in step (2) comprises: mixing the alloy powder and the tetraethyl orthosilicate solution, and sequentially air-drying, drying and sieving to obtain a first powder; The tetraethyl orthosilicate solution is a mixed solution of tetraethyl orthosilicate and ammonia water, and the content of the tetraethyl orthosilicate is 0.5-1.5wt%.

7. The preparation method according to claim 6, characterized in that: The modified water glass coating in step (2) comprises: mixing the first powder and the modified water glass solution, and sequentially air drying, drying and sieving to obtain a second powder; Wherein, the modified water glass solution is a mixed solution of water glass and a modifier, and the content of the water glass is 0.3-1.0wt%; And / or, the modified water glass includes modified sodium silicate water glass and / or modified potassium silicate water glass, and the modification method includes any one of doping modification, polymerization modification or sulfurization modification.

8. The preparation method according to claim 7, characterized in that: The modified silicone resin coating in step (2) comprises: mixing the second powder and the modified silicone resin solution, and sequentially air-drying, drying and sieving to obtain alloy-coated powder; The modified silicone resin solution is a mixed solution of modified silicone resin and an organic solvent, and the organic solvent includes any one of acetone, ethyl acetate or toluene or a combination of at least two thereof, and the content of the modified silicone resin is 0.5-2.0 wt %.

9. The preparation method according to claim 4, characterized in that: The spray granulation in step (3) comprises: mixing the alloy coated powder and the polyvinyl butyral solution for spray granulation, cooling and sieving to obtain granulated powder; Wherein, the polyvinyl butyral solution is a mixed solution of polyvinyl butyral and acetone, and the content of the polyvinyl butyral is 1.0-4.0wt%; And / or, the reduction roasting in step (3) is carried out in an atmosphere of hydrogen or a hydrogen-nitrogen mixture.

10. An application of the soft magnetic alloy material according to any one of claims 1 to 3, characterized in that: The soft magnetic alloy material is used to manufacture an integrally formed inductor.

Citation Information

Patent Citations

  • Preparation method of low-loss powder for producing integrally-formed inductor

    CN111063501A